Acute appendicitis in acute leukemia and the potential role of decitabine in the critically ill patient. Issue 1 (2015) - Warad, Deepti; Kohorst, Mira A.; Altaf, Sadaf; Ishitani, Michael B.; Khan, Shakila; Rodriguez, Vilmarie; Nageswara Rao, Amulya A.
Abstract: Acute appendicitis in children with acute leukemia is uncommon and often recognized late. Immunocompromised host state coupled with the importance of avoiding treatment delays makes management additionally challenging. Leukemic infiltration of the appendix though rare must also be considered. Although successful conservative management has been reported, surgical intervention is required in most cases. We present our experience with acute appendicitis in children with acute leukemia and a case of complete remission of acute myeloid leukemia with a short course of decitabine. Decitabine may serve as bridging therapy in critically ill patients who are unable to undergo intensive chemotherapy. Highlights: Acute appendicitis in children with acute leukemia is uncommon and often recognized late. AML requires intensive chemotherapy which further compromises the clinical state of the patient. Immunocompromised state and intestinal wall leukemic involvement makes treatment challenging. We present a case of remission of AML with a short course of decitabine, a hypomethylating agent. Decitabine may serve as bridging therapy and help achieve disease control in critically ill patients.